Constitutionalism in the Approach and Aftermath of the Civil War (Book collections on Project MUSE., 2013)
This collection of essays shows how the constitutional aspects of the Civil War were part of American politics for a long time before and after the conflict by examining developments from the founding era to the Progressive era. The contributors, both political theorists and historians, consider constitutional issues leading to the Civil War, the crucial role of Abraham Lincoln's statesmanship, and how the constitutional aspects of the War and Reconstruction endured in the late 19th and early 20th centuries.